Massive segmental bone loss due to pantibial osteomyelitis in children reconstructed by medial fibular transport with Ilizarov frame - Atiq Uz Zaman, FCPS; Shahzad Javed, FCPS; Ashfaq Ahmad, MBBS; Amer Aziz, FRCS (Journal of Taibah University Medical Sciences, 2017)
Objectives: Vascularized or non-vascularized fibula transport is a novel procedure for limb salvage but has been associated with high failure rates and complications. Ipsilateral medial fibular transport (IMFT) using Ilizarov apparatus is a modification of the procedure to prevent complications and increase success rate. This article presents the largest series of limb salvage for massive tibial bone loss in children due to pan-osteomyelitis by IMFT with Ilizarov apparatus. Methods: A case series of 12 patients with a mean age of 12 (6–18) years is described. At the first stage of surgery, the excision of all dead bone was performed, and Ilizarov without traction apparatus was applied. In second stage, ipsilateral fibula is gradually transferred to tibial defect with the help of ilizarov olive wires. In the third stage, the freshening of docking sites of fibula to tibia was performed. The minimum follow up was of two years. Results: Hypertrophy of the transported fibula accompanied by full weight bearing and satisfactory joint motion occurred in all patients. Removal of sequestrated bone resulted in control of infection in 27.17 ± 7.76 days. Fibular transport took 16.58 ± 4.14 days. The length of tibial bone loss replaced by fibula was 9.50 ± 2.23 cm. The mean days required for union after freshening of the docking site was 76.58 ± 6.20 days. Conclusions: Ilizarov frame for pan tibial osteomyelitis with bone excision and medial fibular transport works well for limb salvage in children.